2023
DOI: 10.30630/joiv.7.2.1201
|View full text |Cite
|
Sign up to set email alerts
|

Computational of Concrete Slump Model Based on H2O Deep Learning framework and Bagging to reduce Effects of Noise and Overfitting

Abstract: Concrete mixture design for concrete slump test has many characteristics and mostly noisy. Such data will affect prediction of machine learning. This study aims to experiment on H2O Deep Learning framework and Bagging for noisy data and overfitting avoidance to create the Concrete Slump Model. The data consists of cement, blast furnace slag, fly ash, water, superplasticizer, coarse aggregate, fine aggregate, age, slump, and compressive strength. A primary data for concrete mixed design using the fine aggregate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In Figure 10, it is shown that the training and validation loss moves downward in the 51st epoch, and their difference also decreases at that point, and the fluctuation is lower. However, as the graph shows a little noise in the training and validation loss curve in the last six epochs, there can be a chance of being slightly overfitted [70], which was tested later in the model evaluation section. [61] 0.93 11, the high accuracy of the model at the 51st epoch is evidence of no underfitting.…”
Section: The Lstm Network Modelmentioning
confidence: 99%
“…In Figure 10, it is shown that the training and validation loss moves downward in the 51st epoch, and their difference also decreases at that point, and the fluctuation is lower. However, as the graph shows a little noise in the training and validation loss curve in the last six epochs, there can be a chance of being slightly overfitted [70], which was tested later in the model evaluation section. [61] 0.93 11, the high accuracy of the model at the 51st epoch is evidence of no underfitting.…”
Section: The Lstm Network Modelmentioning
confidence: 99%